Pengembangan Karakter Religius Peserta Didik Berbasis Keteladanan Guru Dalam Pembelajaran PAI - Achmad Abidin; Romelah; Khozin (Universitas Insan Budi Utomo, 2024)
This article aims to explain the process of developing students' religious character based on teachers' exemplary behavior in schools. This perspective is founded on the belief that the success of instilling religious character values in the educational process cannot be separated from the example set by teachers for their students.This research is classified as qualitative research employing a case study method and a descriptive-qualitative approach. Data analysis was conducted using a descriptive-analytical technique to comprehensively illustrate the phenomena being studied.The findings reveal that the development of students' religious character based on teachers' exemplary behavior in schools is manifested through various efforts to foster values that contribute to building religious character. These include the practice of regular worship, behavior that aligns with religious teachings, the use of polite language, and mutual respect among school community members. This religious character development is carried out by teachers both inside and outside the classroom through consistent verbal and non-verbal communication, which has a positive impact on students.